Automotive Software Engineering: Real-World Necessity and Significance - Dekkati, Sreekanth (Engineering International, 2022)
The automobile industry is undergoing a fundamental shift as it transitions from a mechanical to a software-intensive business, in which most innovation and competition depend on software engineering expertise. This shift is occurring due to the industry’s shift from a mechanical to an electronic focus. Over the past few decades, the significance of software engineering in the automobile industry has grown substantially. As a result, it has garnered a great deal of interest from academics and industry professionals. Even though a considerable amount of information concerning automotive software engineering has been published in various scholarly journals, there needs to be a comprehensive study of this information. This systematic mapping project aims to classify and analyze the literature linked to automotive software engineering to offer a structured body of knowledge, identify well-established themes, and uncover research gaps. This study considers 679 publications from various academic fields and subfields published between 1990 and 2015. The primary studies were dissected and categorized based on five distinct dimensions of interest. In addition, potential holes in the research, as well as suggestions for directions for further investigation, are offered. The literature mainly focused on three different areas: system and software architecture and design, qualification testing, and reuse. These were the issues that were discussed the most frequently. There were fewer comparative and validation studies, and the research body needs to contain practitioner-oriented suggestions. Overall, the research activity on automotive software engineering has a high industrial relevance, but its scientific quality is relatively lower.